Prenatal Alcohol Exposure Alters Steady‐State and Activated Gene Expression in the Adult Rat Brain. (14th February 2015) - Lussier, Alexandre A.; Stepien, Katarzyna A.; Neumann, Sarah M.; Pavlidis, Paul; Kobor, Michael S.; Weinberg, Joanne
Abstract : Background: Prenatal alcohol exposure (PAE) is associated with alterations in numerous physiological systems, including the stress and immune systems. We have previously shown that PAE increases the course and severity of arthritis in an adjuvant‐induced arthritis (AA) model. While the molecular mechanisms underlying these effects are not fully known, changes in neural gene expression are emerging as important factors in the etiology of PAE effects. As the prefrontal cortex (PFC) and hippocampus (HPC) play key roles in neuroimmune function, PAE‐induced alterations to their transcriptome may underlie abnormal steady‐state functions and responses to immune challenge. This study examined brains from adult PAE and control females from our recent AA study to determine whether PAE causes long‐term alterations in gene expression and whether these mediate the altered severity and course of arthritis in PAE females. Methods: Adult females from PAE, pair‐fed (PF), and ad libitum ‐ fed control (C) groups were injected with either saline or complete Freund's adjuvant. Animals were terminated at the peak of inflammation or during resolution (Days 16 and 39 postinjection, respectively); cohorts of saline‐injected PAE, PF, and C females were terminated in parallel. Gene expression was analyzed in the PFC and HPC using whole‐genome mRNA expression microarrays. Results: Significant changes in gene expression in both the PFC and HPC were found in PAE compared to controls in response to ethanol exposure alone (saline‐injected females), including genes involved in neurodevelopment, apoptosis, and energy metabolism. Moreover, in response to inflammation (adjuvant‐injected females), PAE animals showed unique expression patterns, while failing to exhibit the activation of genes and regulators involved in the immune response observed in control and pair‐fed animals. Conclusions: These results support the hypothesis that PAE affects neuroimmune function at the level of gene expression, demonstrating long‐term effects of PAE on the central nervous system response under steady‐state conditions and following an inflammatory insult.